Factors affecting the participation of school age Ati in secondary and tertiary education in Barangay General Fullon, Hamtic, Antique. - Compas, Rona Kristie R.
Study show that school participation of school age Ati are affected mainly by factors. The availability of basic infrastructures (passable roads) helps facilitate accessibility to services available outside the community like secondary schools. The presence of fundamental social services like day care center, an elementary school or health station satisfies the basic needs of the Ati and exposes them to ways of life beyond their community which in turn can further motivate them so get education. Education is mainly perceived as a road to poverty alleviation. The economic status of the household determines whether the child can be sent to school or not. Individual choices and circumstances of the Ati also affect their decision about schooling too. Factors extraneous to the community, like perception of the non-Ati community and availability of assistance from concerned agencies also have a bearing in school participation of school age Ati.